1983
DOI: 10.2466/pr0.1983.53.2.545
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Reliability of the Kansas Marital Satisfaction Scale

Abstract: Further development of a brief measure of marital satisfaction is reported. The Kansas Marital Satisfaction (KMS) Scale was administered to 106 mothers who participated in a pretest for a nutrition education program. In accordance with previous research, Cronbach alpha estimates of internal consistency reliability were, at .96 or greater, more than adequate; test-retest reliability of the scale was substantial, as indicated by an r of .71 over a 10-wk. interval. Non-significant to moderate correlations of scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…correlations were good, with rs of .63 to .92. The as for the other scales were consistent with most previous research, including the relatively poor reliability found for the individual social desirability scale (11,22). Husbands' and wives' perceptions of marital conflict were significantly correlated in all cases in spite of the low power provided by the ~a r n p l e .~ For wives, the marital conflict scales consistently differentiated distressed and nondistressed marriages in terms of marital satisfaction, as expected from Gottman's (8, 9, 10) research.…”
Section: Resultssupporting
confidence: 85%
“…correlations were good, with rs of .63 to .92. The as for the other scales were consistent with most previous research, including the relatively poor reliability found for the individual social desirability scale (11,22). Husbands' and wives' perceptions of marital conflict were significantly correlated in all cases in spite of the low power provided by the ~a r n p l e .~ For wives, the marital conflict scales consistently differentiated distressed and nondistressed marriages in terms of marital satisfaction, as expected from Gottman's (8, 9, 10) research.…”
Section: Resultssupporting
confidence: 85%
“…It was chosen due to its brevity and simplicity in measuring overall marital satisfaction. The reliability of the KMSS has been relatively high and consistent over time, with alpha coefficients ranging from .89 to .97 (Callahan, 1997;Mitchell, Newell, & Schumm, 1983;Schumm, Bollman, Jurich, & Hatch, 1997;Schumm, Nichols, Schectman, & Grigsby, 1983).…”
Section: Methodsmentioning
confidence: 94%
“…The stressful items endorsed were summed to create a total score indicative of the total of stressors a person encountered in the prior year. Finally, participants who were married or living with a domestic partner were asked to complete the Kansas Marital Satisfaction Scale, a 3-item scale that has been shown to be internally consistent and have adequate test-retest reliability and construct, concurrent, discriminative and criterion validity [30–33]. We also asked whether the participant’s spouse/partner smoked and whether the spouse/partner supported the participant’s efforts to quit smoking on a 5-point Likert scale from 1 = strongly agree to 5 = strongly disagree.…”
Section: Methodsmentioning
confidence: 99%